2001
DOI: 10.1007/s002530100631
|View full text |Cite
|
Sign up to set email alerts
|

The use of transgenic plants in the bioremediation of soils contaminated with trace elements

Abstract: The use of plants to clean-up soils contaminated with trace elements could provide a cheap and sustainable technology for bioremediation. Field trials suggested that the rate of contaminant removal using conventional plants and growth conditions is insufficient. The introduction of novel traits into high biomass plants in a transgenic approach is a promising strategy for the development of effective phytoremediation technologies. This has been exemplified by generating plants able to convert organic and ionic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
89
0
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(94 citation statements)
references
References 135 publications
2
89
0
3
Order By: Relevance
“…Evidently, it remains to be shown that the enhancement seen in the plants described here can also be obtained in the relevant organs of food crops. The fact that the uptake of Cd from contaminated soil is increased in the P10:CKX and W6:CKX transgenic plants indicates that an enhanced root system may also be applicable in phytoremediation (i.e., the cleanup of contaminated soils using plants) (Krä mer and Chardonnens, 2001;Krä mer, 2005), providing independent support for previous merely correlative evidence (Krä mer et al, 1997;Roosens et al, 2003).…”
Section: Cytokinin Status and Root System Size Influence Acquisition supporting
confidence: 67%
“…Evidently, it remains to be shown that the enhancement seen in the plants described here can also be obtained in the relevant organs of food crops. The fact that the uptake of Cd from contaminated soil is increased in the P10:CKX and W6:CKX transgenic plants indicates that an enhanced root system may also be applicable in phytoremediation (i.e., the cleanup of contaminated soils using plants) (Krä mer and Chardonnens, 2001;Krä mer, 2005), providing independent support for previous merely correlative evidence (Krä mer et al, 1997;Roosens et al, 2003).…”
Section: Cytokinin Status and Root System Size Influence Acquisition supporting
confidence: 67%
“…It has been demonstrated in classic genetic studies that only a few genes are responsible for metal tolerance (Macnair et al 2000). Transfer and/or overexpression of genes re sponsible for metal uptake, translocation and sequestration may allow for the production of plants which, depending on the strategy, can be successfully exploited in phytore mediation (Krämer & Chardonnens 2001, Pi lon-Smits & Pilon 2002, Clemens et al 2002, Rugh 2004, Eapen & D'Souza 2005, Cherian & Oliveira 2005, Doty 2008. In this case, special attention must be paid to pro blems related to the introduction of geneti cally modified trees, particularly concerning their legal and social acceptance (Knowles & Adair 2007).…”
Section: Molecular Biology and Genetic Engineering For Phytoremediationmentioning
confidence: 99%
“…Genetic engineering of the metabolism may lead to increased concentrations of ligands important for xylem loading and to decreased levels of ligands leading to vacuolar sequestration causing a retention of heavy metals in the roots [59,62,65,105,106]. Transporters for heavy metals or heavy metal complexes represent other targets for classical breeding and genetic engineering to improve properties of plants envisaged for phytoremediation [107,108].…”
Section: Relevance Of Long-distance Transport For Phytoremediationmentioning
confidence: 99%